PENGARUH STRATEGI PEMASARAN DALAM MENINGKATKAN JUMLAH KONSUMEN (STUDI KASUS PADA HOME INDUSTRY “96 BAKERY”) - Agustina Megawati Pasaribu (Jurnal Niaga & Bisnis (e-journal), 2014)
This study aims to identify marketing strategies that had been done by business owners in marketing their products through social media 96 Bakery instagram and to determine whether there is an increase in the number of consumers in 96 Bakery business. Data and information research consisted of primary data collected directly through 96Bakery business owners are Arlene Natasha and secondary data collected through 96 Bakery product buyers. The method used in this study is associative research with quantitative approach to collecting data through interviews, questionnaires and literature. This study has a variable X marketing strategy by using the marketing mix 4P indicator variable Y and increase the number of consumers with AIDA technique to determine the extent to which social media can be utilized by 96 bakery in marketing their products and increase the number of consumers. From the calculation of simple linear regression, obtained Y = 12 754 + 0.007X means if the marketing strategy is constant, then there will be an increasing number of consumers at 12 754 and if the marketing strategy is increased 1 times the increase in the number of consumers of 0.007. Of t test t value obtained for variable marketing strategy (6.022) is greater than the value of t table (1.9905), or sig. t for the variables of marketing strategy (0.000) is smaller than alpha (0:05). So, for variables significantly influence the marketing strategies in increasing the number of consumers against 96Bakery home industry. Keywords: Marketing Strategy, increasing the number of consumers, 96Bakery.